An energy-efficient wireless communication scheme using Quint Fibonacci number system. (2016) - Bhattacharya, Ansuman; Majumder, Pratham; Sinha, Koushik; Sinha, Bhabani P.; Kavitha, K.V.N.
In this paper, an energy-efficient communication scheme for low-power wireless networks is proposed which is based on encoding the messages in a new number system, called the Quint Fibonacci number system (QFNS), followed by using a concept of Silent Communication. The proposed scheme employs a simple hybrid modulation/demodulation technique using non-coherent FSK and ASK, which leads to the design of a low-power, low-cost wireless communication system that will particularly be suitable for remote/rural healthcare applications. We show that with Additive White Gaussian Noise (AWGN) in channel, our scheme offers about 39.6% energy savings at the transmitter and about 52% energy savings at receiver on an average over the conventional Binary Frequency Shift Keying (BFSK) system, for equal likelihood of all possible strings of binary messages. However, simulation results with different types of messages from various healthcare and agricultural sensor data applications show that we get about 29.82% to 36.23% energy savings at the transmitter and about 56.42% to 64.29% energy savings at the receiver over conventional BFSK.